ANALISIS PERSEDIAAN BAHAN BAKU KEMASAN AIR MINERAL DALAM KEMASAN CUP 220ml MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT. BUANA SULTRA MANDIRI KOTA BAUBAU PROVINSI SULAWESI TENGGARA - Tri Cahyono (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2021)
ABSTRACT Pt. Buana Sultra Mandiri is a company that has the field of mineral water treatment business in cup 220ml packaging. The problem that is often confronted by the company is the delay of packaging raw materials when producing mineral water in cup 220ml packaging. Therefore, the method used by researchers to be able to solve problems that occur in PT. Buana Sultra Mandiri is using economic order quantity (EOQ) method with the aim to know how the company's raw material inventory compares with inventory based on Economic Order Quantity (EOQ) method. Keywords: Supplies, Raw Materials, Economic Order Quantity (EOQ)